UNINTENTIONAL OVERDOSING OF INTRAVENOUS PARACETAMOL IN NEONATES: WHERE IS THE TOXICITY?. Issue 1 (14th December 2015) - Bosch, Barbara; Casteels, Kristina; Allegaert, Karel
Abstract : Introduction: Paracetamol is a readily available antipyretic and analgesic, widely used to treat mild to moderate pain. Unintentional overdosing in neonates occurs, but so far only single case reports have been published. Based on an own case and a bibliographic search, we review the safety and tolerance of unintentiontal overdosing of intravenous paracetamol in neonates. Material and methods: A bibliographic search in PubMed and EMBASE using key words: "Pharmacokinetics paracetamol neonate", "Metabolism paracetamol neonate" and "Effects paracetamol neonate" was performed. Results: Thirty cases of neonatal iv paracetamol intoxication were reported. Overall, the reported number remains limited, but even 10-fold drug errors only rarely result in significant morbidity or mortality. In accidental overdosing only one case of relevant hepatic toxicity has been reported. Conclusion: The reported cases of unintentional paracetamol overdosing in neonates suggests a good safety profile and a population specific tolerance. Acetylcysteine administration is recommended, but the prognosis seems to be better in neonates.